Me Mereduksi Kecanduan Game Online Melalui Layanan Konseling Kelompok Dengan Teknik Behavior Contract Terhadap Siswa Kelas VII SMP 11 Kota Bengkulu: Pendahuluan Metode Penelitian Hasil dan Pembahasan Daftar Pustaka - Yayang Kurnia; Sri Saparahayuningsih; Anni Suprapti (UNIVERSITAS BENGKULU, 2023)
The purpose of this study was to determine the effect of group counseling services using the behavior contract technique in reducing online game addiction for first grade students of SMP Negeri 11 Bengkulu. Researcher used quantitative research with the one-group pretest-posttest experimental method. The research subjects were seven students. The data collection technique used an online game addiction questionnaire. Data analysis used statistics with the t-test formula. The results of this study were proven by the average level of online game addiction in students before being given treatment is in the very high category, after being given treatment the level of online game addiction in students is in the low category. This study proves that there is an influence of group counseling services using the behavior contract technique in reducing online game addiction in first grade students of SMP Negeri 11 Bengkulu. Based on the results of the study. Therefore, it is recommended to use group counseling services with the behavior contract technique in reducing online game addiction. Keywords : Online game addicition, Group Counseling, Behavior Contracting.